SOSIALISASI BAHAYA PENCURIAN LISTRIK PADA INSTALASI KABEL RUMAH TANGGA - Trinil Muktiningrum; Riska Nur Wakidah; Dwi Sari Ida Aflahah; Imam Taufik; Susilowati Susilowati; Alifarose Syahda Zahra; Sepyo Legowo Catur Jaya Sakti; Gistian Rahayu (Jurnal Abdi Insani, 2022)
Since the enactment of Law no. 30 of 2009 regarding electricity, where theft is subject to sanctions, people was increasingly aggressively sabotaging electricity. The regulation cannot be the right solution because there are still many people who do not know that their actions are include in the article on electricity theft, besides the fact that in some place the community has not yet built infrastructure by PLN. The destination of this service is to disseminate knowledge about the dangerous and threats to electricity theft in the household environment. Before carrying out the activity, the Faculty of Engineering with the Dharma Wanita Association of Harbor Masters and Port Authority Class IV Probolinggo regarding the material to be delivered. The implementation is by conveying related material was carried out in a question and answer session of the material presented later. The results of the socialization implementation include: the socialization participants received the activity very openly and enthusiastically. The Chairperson of the Dharma Wanita Union of Harbor Masters and Port Authority Class IV Probolinggo welcomes the offer of cooperation as partners in this community service program and other community service programs that can help develop the insights and abilities of its members. The socialization conditions are conducive for participants. There were no significant obstacles during the implementation of this socialization. Based on observations, participants in the socialization understand the dangers of electricity theft and the legal risks they face. Based on the result of socialization, that activity can increase knowledge regarding the dangers of electricity theft and the legal risks.